Improved mental health among LABILE study participants: a qualitative exploration - Sanatinia,R; Afzal,S; MacLaren,T; McNulty,A; Adele,C; Morah,A; Crawford,M (Personality and Mental Health, 2019)
Results of the LABILE trial showed no difference between people with borderline personality disorder who were prescribed lamotrigine,and those on placebo. However, most study participants experienced sustained improvement in their mental health during the trial.We conducted a thematic analysis of qualitative data from interviews with 47 LABILE study participants to identify factors that may have contributedto this improvement.We identified three main themes: initial reasons and expectations regarding trial participation,patients’experiencesof the trial,and areas of change.Reasons for participating in the trial included a searchfor consistent and stable professional careas well as altruistic motives. Improvements in symptoms over the course of the trial were explained by severalfactors including consistency provided by the research team, salience of the social context,and theavailability of alternative support networks.Whilst participants appreciated the autonomy provided by the voluntary nature of the trial, they felt that improvements stemmedfromthe ‘structure’ brought about by their actively engaging in the study. 2Thisstudy highlights the importance of clear, and transparent communication when treating people with borderline personality disorder. Mental health professionals should ensurethat services for people with borderline personality disorder areconsistentand structured.